A novel technique of taking tendon biopsies in the horse - Becker, C. K.; Cherdchutham, W.; Enzerink, E.; Spek, E. R.; Van Weeren, P. R. (Veterinary and Comparative Orthopaedics and Traumatology, 2001)
To evaluate a novel tendon biopsy technique for use in the horse and to assess the effect of different exercise levels on the healing process of minimally damaged superficial digital flexor tendons (SDFT), 24 Dutch Warmblood foals were randomly divided into 3 equally sized groups one week after birth. One group was box rested, one group got box rest with additional enforced exercise, and one group got free pasture exercise. Biopsies from the peripheral region of the SDFT were taken at age 2 months using a new micro-biopsy technique. At age 5 months the foals were euthanized and samples from the biopsy site and a control site were harvested. Collagen fibrillar index (CFI, the total amount of collagen as a percentage of the measured area), mass-average diameter (MAvD, mean of the diameter versus area distribution) and collagen fibrillar diameter frequency (the distribution of collagen fibril sizes expressed as a percentage of the number of collagen fibrils) were calculated. The CFI, MAvD values were significantly lower in the wound samples. It is concluded that the biopsy technique may be a useful tool for research applications. The absence of exercise-induced effects on the collagen fibril population in the wound samples suggests that the first phase of the process of tendon healing in immature equine SDFT’s sustaining a minor surgically-induced wound, is not exercise-dependent. However, findings may be different in mature horses sustaining accidental trauma.A novel technique to take biopsies from immature equine flexor tendons was developed and used to evaluate the effect of various levels of exercise on the development of the collagen fibril diameter distribution in the resulting wounds. The technique appeared to be minimally invasive, but complication rate was deemed too high for clinical use. There was no effect of exercise on mass average diameter of collagen fibrils, suggesting that the repair process, at least in its initial stage, is exercise-independent.
Keywords: Foal; SDFT; collagen fibril population; tendon healing; biopsy